The Harcourt Brace anthology of drama - 4 0 16; 1955- , Worthen, William B.; 5 (Fort Worth, TX : Harcourt Brace College Publishers, 1996)
A collection of classic plays from the European, American, and Asian repertory, with a selection of contemporary stage writing from around the world; divided into seven units, each focused on a significant moment in the history of drama and theater.
Rev. ed. of: HBJ anthology of drama. 1992.
Includes bibliographical references (p. 1312-1327).
Young Adult;Young Adult.
Keywords: 2 -- 0; 6; Drama -- 20 -- Collections; 20; 2